2022
DOI: 10.1038/s41467-022-33925-2
|View full text |Cite
|
Sign up to set email alerts
|

Biferroelectricity of a homochiral organic molecule in both solid crystal and liquid crystal phases

Abstract: Ferroelectricity, existing in either solid crystals or liquid crystals, gained widespread attention from science and industry for over a century. However, ferroelectricity has never been observed in both solid and liquid crystal phases of a material simultaneously. Inorganic ferroelectrics that dominate the market do not have liquid crystal phases because of their completely rigid structure caused by intrinsic chemical bonds. We report a ferroelectric homochiral cholesterol derivative, β-sitosteryl 4-iodocinna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Subsequently, when the temperature dropped again to 340 K, the position of the diffraction peak returned to its preceding state, implying that compound 1 underwent a reversible phase transition, and the phase transition temperature was consistent with the DSC test results. 36,37 As is well-known, how to clarify the microstructure changes of this high-temperature phase transition without X-ray singlecrystal diffraction is indeed a new challenge. 38 We speculate that the high-temperature reversible phase transition may be caused by the ordered disorder of organic cation groups, which can also be reflected by their Raman bands.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Subsequently, when the temperature dropped again to 340 K, the position of the diffraction peak returned to its preceding state, implying that compound 1 underwent a reversible phase transition, and the phase transition temperature was consistent with the DSC test results. 36,37 As is well-known, how to clarify the microstructure changes of this high-temperature phase transition without X-ray singlecrystal diffraction is indeed a new challenge. 38 We speculate that the high-temperature reversible phase transition may be caused by the ordered disorder of organic cation groups, which can also be reflected by their Raman bands.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thermal-stimulated phase transition materials can be used in various smart devices, including signal processors, switches, and memory devices. 13–19 It is interesting to note that the physical properties of switchable dielectric materials change significantly when external stimuli are applied, including electric fields, temperature, and light. 20–29 Furthermore, it has been shown that a scientifically designed and tuned organic cation enables the material to have multiple properties, including ferroelectricity, pyroelectricity and piezoelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectric LCs have unique application advantages in display and optoelectronics due to their exceptionally fast electro-optical response and the special photoelectric effect. For a long time, compared to other types of LC phases with D ∞h symmetry, the chiral smectic LC phase was thought to exhibit ferroelectricity because of the C 2 -symmetric polarization vector perpendicular to both the director and the molecular layer direction. Subversively, in recent years, ferroelectricity has also been experimentally proved in the nematic LCs with C ∞v symmetry, breaking the conventional thinking of ferroelectric LCs and opening a new chapter in condensed matter science and related applications. The broken head-to-tail symmetry of two permissible director orientations in such a nematic LC system enables the molecular dipoles to spontaneously orient to a preferred direction, generating macroscopic polarization. , Liquid crystals can be generated by heating some organic solid crystals . However, although the respective development of ferroelectric SCs and LCs has made great strides, and most recently a molecular ferroelectric with ferroelectricity in the SC and typical chiral smectic LC phases has been reported, it still remains a great challenge to design a single material with ferroelectricity in both its SC and LC phases. The dual ferroelectricity in one material is fascinating and provides a platform for in-depth studying and understanding of the underlying correlation of the symmetry and polarity between sequential SC and LC phases.…”
Section: Introductionmentioning
confidence: 99%
“… 34 , 40 42 Liquid crystals can be generated by heating some organic solid crystals. 43 However, although the respective development of ferroelectric SCs and LCs has made great strides, and most recently a molecular ferroelectric with ferroelectricity in the SC and typical chiral smectic LC phases has been reported, 44 it still remains a great challenge to design a single material with ferroelectricity in both its SC and LC phases. The dual ferroelectricity in one material is fascinating and provides a platform for in-depth studying and understanding of the underlying correlation of the symmetry and polarity between sequential SC and LC phases.…”
Section: Introductionmentioning
confidence: 99%